2020
DOI: 10.1016/j.corsci.2020.108611
|View full text |Cite
|
Sign up to set email alerts
|

Degradation mechanism of Ti-6Al-2Sn-4Zr-2Mo-Si alloy exposed to solid NaCl deposit at high temperature

Abstract: This study focuses on the corrosion behaviour of Ti-6Al-2Sn-4Zr-2Mo-Si alloy in presence of NaCl deposit in air at 560°C. The active oxidation mechanism at the origin of the corrosion phenomenon enhancement in presence of solid NaCl is thought to be connected to the formation of both external and internal thick oxidation areas. Thermodynamic calculations allowed showing the role played by the different alloying elements in the formation of the external oxide and detailed TEM characterisations brought new insig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 44 publications
0
8
1
Order By: Relevance
“…18 . Although, according to Ciszak C et al 47 , many oxides can be observed according to theoretical calculations, in practice, TiO 2 , ZrO 2 , and Al 2 O 3 have been observed, but only TiO 2 was observed in this study.…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…18 . Although, according to Ciszak C et al 47 , many oxides can be observed according to theoretical calculations, in practice, TiO 2 , ZrO 2 , and Al 2 O 3 have been observed, but only TiO 2 was observed in this study.…”
Section: Resultscontrasting
confidence: 54%
“…Some chlorides might be attributed to exceptionally poor stability as Ti and Al chlorides. Several researchers have explored the corrosion mechanism in Ti alloys with NaCl [46][47][48][49] . An active corrosion process is considered responsible for reducing corrosion protection in the presence of NaCl deposits.…”
Section: Nacl Hot Corrosionmentioning
confidence: 99%
“…Substantial Sn contents were only found near the crack mouth, which might be attributed to the high volatility of SnCl 4 . Although corrosion products containing zirconium were not identified in this work, formation of zirconium oxychlorides and oxides were both observed in previous studies on NaCl-induced corrosion [12,46]. In terms of the activity of Zr and Mo, Ciszak et al pointed out that both Zr and Mo can react with Cl 2 and form corresponding chlorides/oxides at 560 °C based on theoretical thermodynamic modelling.…”
Section: Activities Of Alloying Elementsmentioning
confidence: 58%
“…So for laboratory fatigue testing under relatively low pressures, it has been suggested that pyrohydrolysis reactions are favoured over oxidation, giving rise to HCl formation [15,44]. Nevertheless, reaction (8) with chlorine gas is in principle thermodynamically favoured, especially at higher temperatures [45,46];…”
Section: Crack Propagationmentioning
confidence: 99%
“…The oxidation at 800 specimens was not change appearance color after corrosion The weight change was low in uenced where weight gain was 0.8 mg/ cm 2 . Several types of research 16,49,50 have previously established the deleterious in uence of NaCl deposits on the oxidation resistance of (CP) titanium and titanium alloys. An active corrosion process is considered responsible for reducing corrosion protection in the presence of NaCl deposits.…”
Section: Nacl Hot Corrosionmentioning
confidence: 99%